Compute cos 3 6 ∘ − cos 7 2 ∘ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice, but how do you prove this identity?
Log in to reply
I have provided the proof.
Note that cos 3 6 − cos 7 2 = 2 cos 3 6 + 2 cos 7 2 2 cos 2 3 6 − 2 cos 2 7 2 = 2 cos 3 6 + 2 cos 7 2 cos 7 2 + 1 − cos 1 4 4 − 1 = 2 1 = 0 . 5 . This method is quite slick in my opinion! Source: 103 Trigonometric problems by Titu Andreescu.
Problem Loading...
Note Loading...
Set Loading...
There is a general identity (see proof below):
k = 1 ∑ n cos ( 2 n + 1 2 k − 1 π ) = 2 1
So when n = 2 , we have:
cos 5 π + cos 5 3 π cos 5 π − cos ( π − 5 3 π ) cos 5 π − cos 5 2 π ⟹ cos 3 6 ∘ − cos 7 2 ∘ = 2 1 = 2 1 = 2 1 = 0 . 5
Proof:
S = k = 1 ∑ n cos ( 2 n + 1 2 k − 1 π ) = ℜ ( k = 1 ∑ n e 2 n + 1 2 k − 1 π i ) = ℜ ( e 2 n + 1 π i k = 0 ∑ n − 1 e 2 n + 1 2 k π i ) = ℜ ⎝ ⎛ e 2 n + 1 2 π i − 1 e 2 n + 1 π i ( e 2 n + 1 2 n π i − 1 ) ⎠ ⎞ = ℜ ( e 2 n + 1 2 π i − 1 e π i − e 2 n + 1 π i ) = ℜ ( 1 − e 2 n + 1 2 π i 1 + e 2 n + 1 π i ) = ℜ ( 1 − e 2 n + 1 π i 1 ) = ℜ ( 1 − cos 2 n + 1 π − i sin 2 n + 1 π 1 ) = ℜ ( ( 1 − cos 2 n + 1 π − i sin 2 n + 1 π ) ( 1 − cos 2 n + 1 π + i sin 2 n + 1 π ) 1 − cos 2 n + 1 π + i sin 2 n + 1 π ) = ℜ ( 2 − 2 cos 2 n + 1 π 1 − cos 2 n + 1 π + i sin 2 n + 1 π ) = 2 1